Biomimetic nanothylakoids for efficient imaging-guided photodynamic therapy for cancer. Issue 28 (21st March 2018) - Ouyang, Jiang; Wang, Liqiang; Chen, Wansong; Zeng, Ke; Han, Yajing; Xu, Yan; Xu, Qunfang; Deng, Liu; Liu, You-Nian
Abstract : Biomimetic nanothylakoids are constructed for the first time and show high efficiency in tumor microenvironment modulation and imaging-guided photodynamic antitumor therapy. Abstract : Biomimetic nanothylakoids, which are constructed from the thylakoid membrane of vegetable leaves, show high efficiency in tumor microenvironment modulation and photodynamic antitumor therapy under near infrared fluorescence guidance. Furthermore, their outstanding biosafety, facile preparation and low cost make nanothylakoids suitable for further clinical applications.